Individuating quantities. - Tal, Eran (Philosophical Studies, 2019)
When discrepancies are discovered between the outcomes of different measurement procedures, two sorts of explanation are open to scientists. Either (i) some of the outcomes are inaccurate or (ii) the procedures are not measuring the same quantity. I argue that, due to the possibility of systematic error, the choice between (i) and (ii) is underdetermined in principle by any possible evidence. Consequently, foundationalist criteria of quantity individuation are either empty or circular. I propose a coherentist, model-based account of measurement that avoids the underdetermination problem, and use this account to explain how scientists individuate quantities in practice.